Ensino a distância: experiências e inovações - White, Robert A.; Thomas, Pradip (Comunicação & Educação, 1995)
First part of the article Educational Transmission published by Magazine Communications Research Trends, of the Centre for the Study of Communication and Culture, of the University of St. Louis, USA. The use of radio and TV in educational programs.